Role of Misoprostol in Open Myomectomy in Females Attending a Tertiary Care Hospital - Nasir, Sannia; Masoom, Kausar (Indus Journal of Bioscience Research, 2025)
Background: The benign tumors that affect women most frequently are uterine leiomyomas. In routine practice, misoprostol is not applied during or before open myomectomy. Literature has shown that misoprostol can be beneficial and may effectively reduce blood loss. Objectives: To determine the outcome of misoprostol administration in females undergoing open myomectomy for intrauterine fibroids. Study design & Setting: This descriptive study was conducted at Department of Obstetrics & Gynecology, MNCH Hospital, PIMS, Islamabad from 1st January 2024 to 1st July 2024. Methodology: A total of 125 patients scheduled for open myomectomy were included in the study. A blood sample was taken to assess hemoglobin levels. Patients received 400 µg of vaginal misoprostol an hour before surgery, which was performed by a single team under spinal anesthesia. Operative time and intraoperative blood loss were measured, and post-surgery hemoglobin levels were reassessed. If the hemoglobin drop exceeded 2 g/dl, a blood transfusion was administered. Results: The study included 125 participants with a mean age of 29.48±6.69 years and a mean BMI of 24.66±3.66 kg/m². The mean fibroid size was 9.90±2.98 cm, and the mean duration of fibroids was 28.44±18.24 months. The mean intraoperative blood loss was 628.52±370.93 ml, with 56% of participants experiencing blood loss ≤500 ml. The mean surgery duration was 140.09±53.38 minutes, with 56.8% of surgeries completed within 150 minutes. The mean hemoglobin drop was 1.578±0.87 g/dl, and 26 patients (20.8%) required blood transfusions. No significant adverse effects related to misoprostol were reported.